Review: Guinea-Martin, Daniel (Ed.) (2012). Trucos del oficio de investigador: Casos prácticos de investigación social [Tricks of the Trade: On Social Science Research Practices] - Krizmanics, Georg T. A. (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2013)
"Trucos del oficio de investigador" [Tricks of the Trade] is a handbook on qualitative and quantitative social science methods in which 12 scientists intend to demystify social science research practices by sharing their "tricks" of their research practices. They illustrate their way of working through the research process by reflecting on their own research cases within qualitative and quantitative social science. The authors show that doing research is not so much about originality as it is about hard work. Drawing from the saying that failure is the basis for success, they speak revealingly about their failures and how they engendered their stories of success. These experienced scientists invite the reader to observe their way of doing research while doing it. The authors' openness concerning their own research practices is an appeal to a confidential student-teacher relationship in order to help to undermine the classical student-teacher relationship, by revealing the fallibility of the teacher. This is a step in the democratization of the methodological debate in the social sciences. URN: http://nbn-resolving.de/urn:nbn:de:0114-fqs140153